Sexual dimorphism in Ramphastos toco and Ramphastos dicolorus (Piciformes, Aves) - Castro, Márcio S.; Recco-Pimentel, Shirlei M.; Rocha, Guaracy T. [UNESP] (My University, 2003)
Phenotypic sexual dimorphism seems to be rare in the Ramphastidae family, except in Pteroglossus viridis and in the genus Selenidera. Many breeders of wild birds believe that specimens of Ramphastos toco can be sexed using bill characteristics. In this study, various discriminant phenotypic variables were analyzed in birds which were sexed cytogenetically. Fifty-one specimens of R. toco and 20 R. dicolorus were studied. The statistically significant parameters which served to distinguish the sex in these species were the length of the culmen and tomium, length of the lower corneous beak and the cloaca. Using these parameters, capitive bird breeders can determine sex of R. toco specimens by phenotypic analysis and form breeding couples more quickly.
Keywords: Ramphastidae; Ramphastos; Sexual dimorphism; animal; beak; bird; female; genetics; histology; male; phenotype; sexual development; Animals; Beak; Birds; Female; Male; Phenotype; Sex Characteristics; Animalia; Aves; Enterobacter; Piciformes; Pteroglossus viridis; Ramphastos dicolorus; Ramphastos toco; Selenidera